Experimental investigation on hypersonic shock-shock interaction control using plasma actuator array. (September 2022) - Tang, Mengxiao; Wu, Yun; Wang, Hongyu
Abstract: In this paper, the hypersonic shock-shock interaction control using plasma actuator array is experimentally studied to explore a new surface thermal protection method of hypersonic aircraft. The typical flow structure is produced by a double-wedge model abstracting from the rudder component, and the high schlieren imaging, as well as pressure-sensitive paint/temperature-sensitive paint measurement system, are adopted for flow diagnostics with and without actuation. The results shows that the shock-shock interaction system can be controlled by the plasma actuator array in Ma  = 6.0 and Ma  = 8.0, and the latter case has a better control outcome where the complicated shock-shock interaction system can be modified to one single oblique wave structure. It indicates that the heat flow amplification effect induced by shock-shock interaction can be alleviated. Also, the increase in energy deposition is proved to have a positive impact on the control outcome, namely the higher energy deposition brings in a better control effect. At last, a preliminary conceptual model is established to reveal the probable thermal protection mechanism. The virtual curved compression surface produced by the high-energy plasma actuator array plays an important role in achieving shock-shock interaction control. Highlights: A hypersonic surface thermal protection method via shock-shock interaction control using plasma actuator array is proposed. The complicated shock-shock interaction system can be modified to one single oblique wave structure. A conceptual model is established to reveal the mechanism of shock-shock interaction control.